Bacterial etiology and antibiotic susceptibility pattern of diabetic foot infections in Tabriz, Iran - Akhi, Mohammad Taghi (GMS Hyg Infect Control, 2015)
Aim: The aim of this study was to investigate anaerobic and aerobic bacteria profile and determination of antibiotic susceptibility pattern in aerobic bacteria. Method: Specimens were cultured using optimal aerobic and anaerobic microbiological techniques. Identification of bacterial isolates was performed by standard microbiological methods and antibiotic susceptibility testing was performed according to the guidelines of Clinical and Laboratory Standards Institute (CLSI). Result: 92 bacterial strains were isolated from 60 samples of diabetic foot ulcers. Predominant aerobic bacteria isolated from these infections were S. aureus (28%) followed by Enterobacteriaceae family (24%) including Escherichia coli (15%), Citrobacter spp. (4%), Enterobacter spp. (4%), and coagulase-negative Staphylococcus spp. (17%), Enterococcus spp. (15%), Pseudomonas aeruginosa (7%) and Acinetobacter spp. (4%). No Clostridium spp. were isolated and 4% Bacteroides fragilis obtained from anaerobic culture. All Gram-positive isolates were susceptible to linezolid while all Enterobacteriaceae showed sensitivity to imipenem. Conclusion: Most of DFIs specimens were poly microbial infection and predominant bacteria were S. aureus and B. fragilis. These wounds may require use of combined antimicrobial therapy for initial management.